Droplet-assisted electrospray phase separation using an integrated silicon microfluidic platform. Issue 1 (12th December 2021) - Zhang, Yan; Kim, Sungho; Shi, Weihua; Zhao, Yaoyao; Park, Insu; Brenden, Christopher; Iyer, Hrishikesh; Jha, Prasoon; Bashir, Rashid; Sweedler, Jonathan V.; Vlasov, Yurii
Abstract : We report on a silicon microfluidic platform that enables integration of transparent μm-scale microfluidic channels, an on-chip pL-volume droplet generator, and a nano-electrospray ionization emitter that enables spatial and temporal phase separation for mass spectrometry analysis. Abstract : We report a silicon microfluidic platform that enables monolithic integration of transparent micron-scale microfluidic channels, an on-chip segmentation of analyte flows into picoliter-volume droplets, and a nano-electrospray ionization emitter that enables spatial and temporal separation of oil and aqueous phases during electro-spray for subsequent mass spectrometry analysis.